2012
DOI: 10.1007/s13224-012-0290-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of 17 α Hydroxy Progesterone Caproate (17OHPC) in the Prevention of Preterm Labor

Abstract: Objective To evaluate the role of 17 a hydroxyprogesterone caproate (17OHPC) in the prevention of preterm labor in high risk asymptomatic patients with a history of preterm delivery. Methods The study included 96 patients with a singleton pregnancy and having a prior preterm birth. They were divided in 2 groups, group I (treatment group) included 46 asymptomatic patients who were given 17OHPC injections starting from 16-20 weeks till 36 weeks and group II (control group) included 50 patients who did not receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…According to the study by Nigar et al, the prevalence of preterm delivery was 6.9% in India; the mean gestational age at birth in the 17-OHPC receivers and controls were 36 weeks and 33 weeks plus five days respectively; the gestational age at birth was significantly higher in the case group than in the control group, (23) which is inconsistent with the current study results.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the study by Nigar et al, the prevalence of preterm delivery was 6.9% in India; the mean gestational age at birth in the 17-OHPC receivers and controls were 36 weeks and 33 weeks plus five days respectively; the gestational age at birth was significantly higher in the case group than in the control group, (23) which is inconsistent with the current study results.…”
Section: Discussioncontrasting
confidence: 99%
“…Oral progesterone are easy to take but are less effective because of first pass hepatic metabolism leading to variable plasma levels while intramuscular progesterone carries the risk of swelling and bruising at injection site. 17 There are various studies available which prove role of oral and intramuscular progesterone in the prevention of preterm birth independently or in combination with control groups but there was no comparative data available.…”
Section: Discussionmentioning
confidence: 99%
“…A study was done in India in which 23 of 46 women treated with 17 α-hydroxyl progesterone (intramuscular) delivered pre-term (50%) when compared to a control group. 17 Various studies also prove role of oral progesterone in reducing the risk of PTB for example PTB occurred in 29 out of 47 (39.2%) using oral progesterone versus a controlled group 44 PTBs out of 74 (59.5%). 18 In order to compare the effectiveness between two routes of progesterone, Maher et al concluded that daily vaginal progesterone administration is associated with lower rates of PTBs as compared to intramuscular weekly progesterone administration after a randomized trial of 502 singleton pregnant women.…”
mentioning
confidence: 99%